Variation in the use of infection control measures and infection-related revision incidence after breast implant surgery in the Netherlands. (December 2022) - Becherer, Babette E.; Marang-van de Mheen, Perla J.; Young-Afat, Danny A.; van der Hulst, Rene R.J.W.; Keuter, Xavier H.A.; Rakhorst, Hinne A.; Mureau, Marc A.M.
SUMMARY: Background: The use and effect of most infection control measures (ICMs) in breast implant surgery are still debated, likely resulting in undesired variation in current practices. Objectives: This study investigated the relationship between the number and combinations of ICMs used and the infection-related revision incidence after breast implant surgery. Additionally, national variation between Dutch healthcare institutions in ICM use was evaluated. Methods: For this multicentre, population-based study, all patients who received a primary breast implant or tissue expander for breast augmentation or reconstruction between 2015 and 2019 were identified from the Dutch Breast Implant Registry. Seven prospectively collected ICMs were investigated: preoperative antibiotics, implant and/or pocket irrigation, glove change, nipple guards, insertion sleeve, postoperative drains, and postoperative antibiotics. Results: This study included 52, 415 implants (85% augmentation, 15% reconstruction).The median (IQR) number of ICMs used was 3 (3-4) for augmentation and 4 (4-5) for reconstruction. Median follow-up was 30 months for augmentation and 34 months for reconstruction. Infection-related revision incidence was 0.1% for augmentation and 2.1% for reconstruction. Most infection-related revisions occurred within 2 months for augmentation and 2.5 months for reconstruction. The impact of ICM use on infection-related revision incidence remained unclear, given its low incidence. A significant variation was observed between institutions in the use of postoperative antibiotics and drains. Conclusions: Although the use of different ICMs varied considerably between institutions, the infection-related revision incidence after breast implant surgery was generally low. Most surgeons used four ICMs for breast reconstruction and three ICMs for breast augmentation. Further studies on the causes and effects of the observed variation are needed.